PROBLEM OF TREATMENT WITH STATINS IN RUSSIA: WILL GENERICS HELP? - S. Y. Martsevich (Рациональная фармакотерапия в кардиологии)
The article underlines necessity of statins treatment for patients with high risk of cardio-vascular events. It is noted that in our country these drugs are used extremely seldom. The problem of generic-statins equivalence to original drugs is considered.